Interregional Interaction in Ancient Mesoamerica - Englehardt, Joshua D.; Carrasco, Michael D (University Press of Colorado, 2018)
Archaeologists have long recognized the crucial role of interregional interaction in the development and cultural dynamics of ancient societies, particularly in terms of the evolution of sociocultural complexity and economic systems. New Perspectives on Interregional Interaction in Ancient Mesoamerica builds on and amplifies this earlier research to examine such sociocultural phenomena as movement, migration, symbolic exchange, and material interaction in their role as catalysts for variability in cultural systems. The contributors contend that interregional cultural exchange in Pre-Columbian Mesoamerica played a key role in the creation of systems of shared ideologies, the production of regional or "international" artistic and architectural styles, shifting sociopolitical patterns, and changes in cultural practices and meanings.